Analysis of Factors Affecting Information System Security Behaviour in Employees at IT Company - Melissa Indah; Aileen Angelina; Gavrilla Claudia; Devita Sertivia; Jevelin Jevelin (Universitas Multimedia Nusantara, 2022)
Abstract—Information is an essential element for organizations today. Confidentiality, integrity, and availability of information have a vital role in supporting organizational performance. Therefore, it is necessary to take information security measures so that the use of information can run effectively, efficiently, and integrated. The more valuable the information, the more security standards are needed to protect it. Among other things, the purpose of computer security is to protect information. The higher the security standards provided, the higher the protection of the privacy of that information. Protecting company employees' privacy is one factor that must be considered in the implementation of information systems. PT Telkomsel is one of the companies that experienced a data breach. This report will discuss nine hypotheses to determine the factors that affect Information System Security Behavior for employees of PT Telkomsel. Thus, validity, reliability, and hypothesis tests were carried out using the SmartPLS 3 software. The results showed a significant influence between the Security Education and Training variables on Information Security Awareness, Employee Accountability, and Employee Relationships. Index Terms—Information System Security Behavior, Security Education & Training, Information Security Awareness, Employee Relationships, Employee Accountability, Organizational Culture, National Culture